Contributo Allo Studio della Vegetazione Dei Calcari Dolomitico-Giurassici della Sardegna: Vegetazione Del “Texile” di Aritzo E- “Toneri” di Belvì (Sardegna Centrale) (Giornale botanico italiano, 1956)
Summary The vegetation of dolomitic and jurassic calcareous rocks has been studied and, particularly, the flora of Aritzo's and Belvi's ?Toneri? both located in the middle east of Sardinia. The flora of Aritzo's Toneri is very scanty because the calcareous tower-like blocks lie on a schistic ground and are very narrow. The predominant species are those with a short annual cycle: the only exception being the Quercus Ilex, growing on the walls of the calcareous rocks. The flora of Belvi's ?Toneri?, on the contrary, is more copious because this is larger than Aritzo's Toneri and here the erosions are less evident. As a matter of fact, here, besides the Quercus Ilex, there are some commun species of the ?macchia?. The flora of neighbouring schistic mountains is very different. The difference in the chemical characteristics of ground, as the Author claims, does not justify the great difference observed between the flora of calcareous and schistic ground. The last is typicaly mesophylic, Quercus Robur var. lanuginosa, Castanea sativa, Juglans regia, Ilex Aquifolium have been chiefly found. In the same region at a higher altitude xerothermic species, like Quercus Ilex, have been observed. The Author points out that the typical characteristic of Toneri's flora depends upon geological factors more than chemical or climatic one. In agreement with this point of view the Author found the same vegetation in Oliena, Tuttavista, Albo and Other dolomitic-jurassic calcareous Mountains of Sardinia.
doi: 10.1080/11263505609431614

Buxus Balearica Willd., Elemento Mediterraneo-Occidentale della Sardegna - Martinoli, Giuseppe (Giornale botanico italiano, 1950)
Summary The occurance of Buxus balearica Willd. in Sardinia, already reported by Gennari (1864), and its indigenous state are confirmed by the present study. Its station and geographic distribution as well as the biocenosis in which this species takes part (Barbusi near Sulcis in S. Sardinia) are considered. The study of the Barbusi station, in comparison with others hitherto known, brings a general confirmation to Chiarugi's view concerning the mountainous origin of the mediterranea elements. Besides, it emphasizes the differences between the stations of B. balearica, an element of the mediterranea ?macchia?, and those of B. sempervirens, an undergrowth element of mesophilous formations (deciduous woods), which only rarely belonges to more termophilous bioceneses. The author notes that both species belong to the same stage of Q. Ilex and that the altitude range in which the Q. Ilex stage is comprised is very wide in the different mediterranean regions. In addition, the author emphasizes that Buxus sempervirens occurs in Corsica and Atlas up to the upper limit of Quercetum Ilicis, together with species belonging to higher stages, whilst Buxus balearica belongs to the lower limit of Quercetum Ilicis in the underzone ?Olea-Ceratonia?. The altimetric separation of these species is, therefore, obvious. Due to the compenetration of floras of mountainous origin during the phases of the Ice-period, the knowledge of the segregation epoch of these species from each other is made impossible. Buxus balearica occupies actually as eocene substratum and, therefore, shows edaphic exigences for soils of a certain age: a condition not occurring for Buxus sempervirens. Both Buxus species, together with other horeal-tertiary ones (all constituting actually, in the mediterranea countries, a special relict flora) belong to the Lauretum, in a historic sense (Chiarugi).
doi: 10.1080/11263505009431487doi: 10.1080/11263505009431487The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Buxus balearica; geographic distribution; origin (PG); Sardinia